1102. Reconstitution of CMV-specific cell-mediated immunity during letermovir prophylaxis in hematopoietic stem cell recipients. (31st December 2020) - Abidi, Maheen; Gutman, Jonathan; Weinberg, Adriana
Abstract: Background: Patients who are cytomegalovirus (CMV) seropositive (R+) prior to hematopoietic cell transplant (HCT), have 30% incidence of clinically significant CMV reactivation in the absence of prophylaxis. At our institution, letermovir prophylaxis through Day 100 is used in CMV R+ high-risk (HR) (cord blood, haplocord, haploidentical) HCT recipients. We hypothesized that clinically nonsignificant CMV reactivation during letermovir prophylaxis may lead to reconstitution of CMV specific cell mediated immunity (CMV CMI), which may protect the host against CMV disease after letermovir discontinuation. Methods: Blood samples from CMV R+ HR HCT recipients on letermovir were tested by dual color CMV specific IL2/IFNg FLUOROSpot pre-transplant and on Days 100, 182 and 360 post-transplant. Clinical and virologic information were obtained from medical records. Results: Among 35 participants enrolled to date, 19 were eligible for this analysis, which included only participants with CMV CMI defined as ≥20 spot-forming cells/10 6 PBMC pre-transplantation and follow up ≥180 post-transplantation. Median age was 51.5 years (range 22-75), 9 were women, 9 were white non-Hispanic, 8 were Hispanic and the most common underlying malignancy was acute myeloid leukemia (n=10). 14 participants had CMV CMI reconstitution at Day 100; including 5 with and 9 without low level CMV DNAemia, defined as < 5000 international units/ml in whole blood quantitative polymerase chain reaction assay, while on letermovir prophylaxis. Among the 14 participants, 11 remained free of clinically significant CMV reactivation for a median (range) of 260 (80; 260) days post-letermovir discontinuation, while 3 developed acute graft vs. host disease (aGvHD) followed by clinically significant CMV reactivation. 5 participants did not reconstitute CMV CMI at Day 100 and none of them had DNAemia while on letermovir. 1 of 5 participants without CMV CMI reconstitution or aGvHD developed CMV disease after letermovir discontinuation. Conclusion: High-risk patient populations can reconstitute CMV CMI while on letermovir. Ongoing investigation will help establish predictive parameters for CMV CMI that may allow risk stratification for CMV monitoring and letermovir usage. Disclosures: Maheen Abidi, MD, Merck (Research Grant or Support) Jonathan Gutman, MD, Merck (Research Grant or Support) Adriana Weinberg, MD, GSK (Grant/Research Support)merck (Grant/Research Support)